¿why bioethics and law? - Casado González, María (Acta Bioethica, 2002)
Bioethics tends to recognize the plurality of moral options present in today's societies, impeling the need to establish minimum consents. The proceedings that will allow consensual decisions have fundamental importance. If there is no agreement, legislation should establish the allowable limits; therefrom derives the close relationship between Bioethics and Law, understood as a code of conduct emanating from the collective will. It is important to connect the notions of Bioethics and Law, not to juristify the first one, but to understand the constitutional values and the "general principles of civilized nations" as a minimum agreement: in the light of the Declaration of Human Rights and the other International Declarations and Conventions that form part of our common inheritance. Human Rights are both the juridical basis and the minimum ethical consensus essential for democratic societies that cannot be waive.